Ashwagandha as an Adaptogen: Its Influence on Sleep Patterns, Stress Response, and Anxiety in Modern Life - Haber, Mateusz; Czachor, Adrianna; Kula, Paula; Juśkiewicz, Adam; Grelewicz, Olga; Kucy, Natalia; Servaas, Elwira; Kotula, Alicja; Siemiątkowski, Robert (Journal of Education, Health and Sport, 2024)
Background: Ashwagandha (Withania somnifera), a prominent adaptogen in traditional Ayurvedic medicine, has gained substantial attention for its potential to enhance resilience to modern stressors, improve sleep quality, and alleviate anxiety. Preclinical and clinical studies have demonstrated that Ashwagandha’s active compounds, particularly withanolides, influence the hypothalamic-pituitary-adrenal (HPA) axis, leading to reductions in cortisol levels and a more balanced stress response. Puropose: This review aims to consolidate current evidence on Ashwagandha’s efficacy in modulating stress response, improving sleep patterns, and reducing anxiety levels. Material and methods: The review was based on the analysis of materials collected in the databases "Pubmed", Google Scholar, ResearchGate, books and other scientific articles. The search was conducted using keywords: “Ashwagandha”, “Withania somnifera”, “adaptogen”, “stress”, “anxiety”, “sleep”, “cortisol”. “HPA axis”. Results: A review of the literature has shown Ashwagandha anxiolytic properties, with effects comparable to standard anti-anxiety medications but with fewer side effects. Additionally, Ashwagandha has been shown to significantly improve sleep onset latency, sleep duration, and overall sleep quality, particularly in individuals suffering from stress-induced sleep disorders. Conclusions: Ashwagandha shows significant potential as a natural therapy for managing stress, improving sleep quality, and reducing anxiety, primarily through its effects on the hypothalamic-pituitary-adrenal (HPA) axis and cortisol regulation. Clinical trials have demonstrated its efficacy in improving sleep patterns and reducing anxiety, with a generally favorable safety profile. However, there is a need for further research, particularly to better understand the long-term effects and safety of Ashwagandha supplementation.